Safety of 2-level Anterior Cervical Discectomy and Fusion (ACDF) Performed in an Ambulatory Surgery Setting With Same-day Discharge. Issue 3 (April 2019) - Vaishnav, Avani; Hill, Patrick; McAnany, Steven; Gang, Catherine H.; Qureshi, Sheeraz
Abstract : Study Design: This was a retrospective review of prospectively collected data. Objective: To evaluate differences in patient factors, procedural factors, outcomes and safety in 2-level anterior cervical discectomy and fusion (ACDF) performed in ambulatory surgery centers (ASCs) versus the hospital setting. Background: Emphasis on reducing health care costs has led to numerous surgeries across specialties being performed in ASCs. Because of short operative times and moderate postoperative pain, 1-level ACDF is one of the most common spine surgeries successfully performed in ASCs. Despite the success of single-level ACDF, concerns over postoperative complications, including respiratory compromise have curtailed the performance of 2-level ACDF in ASCs. Materials and Methods: Patient demographics, operative factors and outcomes [blood loss, operative time, length of stay, complications and patient-reported outcomes (PROs)] of patients undergoing 2-level ACDF in an ASC and a hospital were compared using the Fisher exact test for categorical and the Student t test for continuous variables. Results: Of the 83 patients included, 25 underwent 2-level ACDF in an ASC, and 58 in a hospital. Mean age for the ASC group was 51.7±7.6 and 53.2±7.9 years for the hospital group ( P =0.44). Body mass index was lower in the ASC group, at 27.3 kg/m 2 versus 30.4 in the hospital group ( P =0.03). Likewise, the ASC group had a lower ASA grade, favoring ASA 1 and 2 ( P <0.001). There were no differences in blood loss ( P =0.72) or complication rates, ( P =0.16) with urinary retention being most common, and only 1 patient in the hospital setting requiring reintubation. In addition, no patients in the ASC setting required hospitalization. There were no differences in preoperative, 6-week and 6-month PROs. Conclusions: The results of our study suggest that 2-level ACDF can be performed safely in the ASC setting without increased risk of complications compared with the hospital setting in an appropriately selected patient. Specifically, body mass index, and ASA class should be taken into consideration. Importantly, the setting of the surgery does not impact early PROs. Level of Evidence: Level 3.